Degradation of aqueous methyl tert-butyl ether by photochemical, biological, and their combined processes - Azadeh Asadi; Mehrab Mehrvar (International Journal of Photoenergy)
The degradation of aqueous methyl tert-butyl ether (MTBE) at relatively high concentrations was investigated by various photo-induced oxidation processes such as UV/H2O2 and UV/TiO2 as well as biological processes and their combination. It was shown that the degradation of MTBE by UV/H2O2 and TiO2 photocatalytic followed a first-order model with apparent rate constant of 1.31×10−1 and 1.21×10−2 min-1, respectively. It was observed that UV/H2O2/TiO2 process did not have any advantages over each of the other processes alone. The biodegradation of methyl tert-butyl ether (MTBE) was evaluated using aerobic mixed culture with three different approaches, including ultimate biological oxygen demand (BODU) assessment, nonacclimated, and acclimated mixed cultures. The apparent rate constant for the biodegradation of MTBE by nonacclimated mixed culture was 4.36×10−2 day-1. It was shown that the acclimatization of the mixed cultures enhanced the rate of biodegradation of MTBE to 3.24×10−1mg L-1h-1. Finally, the effects of the photocatalytic pretreatment of aqueous MTBE on its subsequent biological treatment were studied. It was observed that the rate of bioreaction was not enhanced and the photocatalytic pretreatment had adverse effects on its biological treatment so that the apparent rate constant decreased to 2.83×10−1 mg L-1h-1.